2017
DOI: 10.1021/acssuschemeng.7b03027
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of a Stainless Steel Mesh-Supported Co3O4 Microrod Array As a Highly Efficient Catalyst for Electrochemical Water Oxidation

Abstract: With the rising energy crisis and increasingly serious environmental issues, clean energy sources like fuel cell and lithium–air batteries are attracting the attention of the whole world. The direct fuel cell, especially, is believed to be the quintessential replacement for conventional sources of energy because of its high energy conversion capacity. Electrochemical water splitting has an important role in such sustainable energy technologies. Catalysts play a worthwhile role in water splitting, especially th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…49 Additionally, a wide range of different synthetic methods was applied on Co 3 O 4 in the course of individual studies, including molten salt (MS), 50 ball milling (BM), 51 sol–gel (SG), 52 thermal decomposition (TD), 53,54 precipitation, 55 and classic/microwave hydrothermal (MW) synthesis. 56,57,21…”
Section: Introductionmentioning
confidence: 99%
“…49 Additionally, a wide range of different synthetic methods was applied on Co 3 O 4 in the course of individual studies, including molten salt (MS), 50 ball milling (BM), 51 sol–gel (SG), 52 thermal decomposition (TD), 53,54 precipitation, 55 and classic/microwave hydrothermal (MW) synthesis. 56,57,21…”
Section: Introductionmentioning
confidence: 99%
“…. ARTICLES (Table S1) [27,33,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. The results indicated that the VO-rich Co 2 AlO 4 possessed a high OER kinetics.…”
Section: Methodsmentioning
confidence: 96%
“…4). 165 For comparison, Co 31 to support CoMo catalyst. 185 The 20Ti-SBA-15 (Si/Ti molar ratio 20) was prepared via hydrolysis and aging in MW reactor from TEOS and TTIP in presence of Pluronic P123 structure directing agent.…”
Section: Metal Supportedmentioning
confidence: 99%
“…Fair number of attempts have also been made to prepare supported simple metal oxide (CoO x , Co 3 O 4 , NiO, Fe 3 O 4 , SnO 2 , CeO 2 , TiO 2 ) nanocatalysts for application in petrochemical industry. 75,[160][161][162][163][164][165][166] In order to improve the catalytic activity as well as versatility in application potential of simple metal or metal oxide nanocatalysts, investigations on supported bimetal, [171][172][173][174][175][177][178][179][180][181][182][183][184][185][186][187] mixed metal oxide [188][189][190][191][192][193]196,197 and ternary metal 198,199 nanocatalysts are also available. MW assisted synthesis has been claimed to be economically viable short green method to produce supported nanocatalyst.…”
Section: Catalysis By Supported Simple Metal Catalystsmentioning
confidence: 99%